Anak-anak yang Terpinggirkan: Pembacaan Dekonstruksi terhadap Fabel Aesop The Ant and The Grasshopper - Nafis, Rafi Raihan (Jurnal Bahasa dan Sastra, 2024)
Fabel is one genre in children literature that is utilized to teach moral values to children. Animals in fable are metaphors of the value in society so that they can internalize the value and identify themselves with the ideal value or the logos one. This research is qualitative research. Source of data is from a children fable entitled The Ant and the Grasshopper that is retold by Jan Payne. The data is collected using literature review method. The data are analyzed descriptive-interpretatively using Derrida deconstruction reading. Derrida’s deconstruction reading uncovers the instability of meaning in the fable which ends up marginalizing children. The binary opposition is used in the fable to maintain the stability of logos meaning, namely the importance of diligence and hard work. Meanwhile, the other part of the binary opposition is laziness which is used as the marginalized part. This part is used to assert the logos. Apart from that, other meanings that disturb the instability of meaning are marginalized, one of which is the gray area. This fable shows that there is a possible gray area that is an alternative between working hard and being lazy at work or spending time relaxing. However, to emphasize the center, this gray area is also marginalized. As a result, voiceless children have no choice but to identify themselves with the discourse expressed in the fable. Thus, this logos construction can be said to impose values on children. On the other hand, children themselves do not have the capacity and power to provide counternarratives because cognitively they have not yet developed and they do not have a voice to deliver their concern because the narration is dominated by adult writer.